Hemiagenesis of thyroid with dual thyroid ectopia: A rare case report - Jha, Pankaj S; Rote-Kaginalkar, Varsha; Titare, Prashant; Jadhav, Manoj B (Indian Journal of Radiology and Imaging, 2018)
Developmental defects of the thyroid gland are very rare. The common developmental abnormalities are ectopic thyroid, hemiagenesis and agenesis of thyroid gland. These developmental defects may or may not be associated with deranged thyroid function tests. Ultrasonography (USG) is the initial modality of choice for thyroid hemiagenesis but further evaluation by computed tomography (CT) scan or nuclear scan should be done to look for ectopic thyroid tissue rest. Here, we report a rare case of a 9-year-old female having hemiagenesis of the right thyroid lobe and isthmus along with dual ectopic thyroid tissue at prehyoid and infrahyoid regions of the neck presenting as a midline neck swelling and subclinical hypothyroidism.
Keywords: Ectopic thyroid; subclinical hypothyroidism; thyroid hemiagenesis